(untitled) (Revista da Faculdade de Medicina Veterinária, Universidade de São Paulo, 1970)
The electrophoretic patterns of the blood serum proteins of thoroughbred mare during pregnancy and post partum periods have been carried out. The data obtained have not shown statistical significance.